2013
DOI: 10.4304/tpls.3.3.521-532
|View full text |Cite
|
Sign up to set email alerts
|

English Language Teachers’ Conceptions of Research

Abstract: This article was conducted on 150 EFL teachers investigating the conceptions of research. An understanding of this issue is very important to the development of conditions for encouraging teachers to be research engaged in order not to be subservient and take a much more pioneering role in curriculum development. Questionnaire responses were analyzed to determine the teachers' view of research. The findings of this research present that the teachers' conceptions of research are very close to conventional scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 9 publications
(1 reference statement)
0
12
0
Order By: Relevance
“…Findings from the educational research in language learning can assist teachers in providing evidence‐based justifications for the curriculum materials they choose and the pedagogical decisions they make. Such information enables teachers to better defend their professional choices to skeptical colleagues, parents, and administrators, and capacitates them to exercise more authoritative influence regarding policy‐related decisions (Bengo, Herrera, & Santos, ; Tabatabaei & Nazem, ). Most importantly, research findings can enable teachers at all levels to move past a position in which the only evidence that they may have for the effectiveness of their teaching is that “the kids loved it!” toward a professional stance in which the rationale for their instructional decisions is thoroughly grounded in the collection and analysis of information from research findings, and from careful analysis of their own classroom practices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from the educational research in language learning can assist teachers in providing evidence‐based justifications for the curriculum materials they choose and the pedagogical decisions they make. Such information enables teachers to better defend their professional choices to skeptical colleagues, parents, and administrators, and capacitates them to exercise more authoritative influence regarding policy‐related decisions (Bengo, Herrera, & Santos, ; Tabatabaei & Nazem, ). Most importantly, research findings can enable teachers at all levels to move past a position in which the only evidence that they may have for the effectiveness of their teaching is that “the kids loved it!” toward a professional stance in which the rationale for their instructional decisions is thoroughly grounded in the collection and analysis of information from research findings, and from careful analysis of their own classroom practices.…”
Section: Introductionmentioning
confidence: 99%
“…University researchers often wonder why so few research findings seem to make their way into classroom practice, while K–12 teachers express frustration with how “out of touch” academic articles seem to be with the day‐to‐day realities of K‐12 classrooms. There is tremendous consensus surrounding the existence of this gap in language education, as well as the reasons for it, in findings from studies in countries as diverse as Argentina (Banegas, ); Bangladesh (Anwaruddin & Pervin, ), Canada (Dagenais, Lysenko, Abrami, Bernard & Janosz, ); Light & Gnida, ; Witherow, ), England (Castle, ; Reis‐Jorge, ; Tavakoli & Howard, ), Iran (Tabatabaei & Nazem, ), Israel (Shkedi, ); the Philippines (Bengo et al, ), Saudi Arabia (Borg & Alshumaimeri, ); Turkey (Kutlay, ), and the United States (Drill, Miller, & Behrstock‐Sherratt, ).…”
Section: Introductionmentioning
confidence: 99%
“…The teachers 78 reported that a lack of time, knowledge, and access to material are key factors limiting their ability to be research-engaged. In addition, Tabatabaei and Nazem (2013) investigated 150 English as a Foreign Language (EFL) teachers' conceptions of research and they found teachers' conceptions of research are very close to the conventional scientific theories and findings. Meanwhile, lack of time, knowledge, and institutional support are the influential factors which restrict teachers' abilities to be research-engaged.…”
mentioning
confidence: 98%
“…One can refer to Tabatabaei and Nazem's (2013) study as an example of a research conducted in an EFL context to obtain teachers' perceptions about the relationship between SLA research and language pedagogy. Investigating the conception of 150 English language teachers, Tabatabaei and Nazem study 's (2013) showed that teachers referred to lack of research knowledge, time, and support by their institutions as the foremost reasons for restricting their engagement in doing SLA research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to some researchers (e.g., Davis, 1995;Shavelson & Towne 2002;Tabatabaei & Nazem, 2013;Thomas & Pring 2004), teachers are not just responsible to deliver the assigned curriculum but also to deal with the classroom problems. They need to implement measures successfully to solve the problems which they may face in their L2 classrooms.…”
mentioning
confidence: 99%